2020
DOI: 10.1145/3427335
|View full text |Cite
|
Sign up to set email alerts
|

VibHand: On-Hand Vibrotactile Interface Enhancing Non-Visual Exploration of Digital Graphics

Abstract: Visual graphics are widely spread in digital media and are useful in many contexts of daily life. However, access to this type of graphical information remains a challenging task for people with visual impairments (VI). In this study, we designed and evaluated an on-hand vibrotactile interface that enables users with VI to explore digital graphics presented on tablets. We first conducted a set of exploratory tests with both people with VI and blindfolded (BF) people to investigate several design factors. We th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Generally, these studies focused on raisedline graphics of common objects (usually from Snodgrass et al [41]) or patterns (i.e. specific graphic combinations [31] [47]) which participants had to recognize. The studies were based on comparative studies involving people with different visual capacities, such as early blind, late blind and sighted people, which showed contradictory results.…”
Section: Recognition Of Tactile Graphicsmentioning
confidence: 99%
“…Generally, these studies focused on raisedline graphics of common objects (usually from Snodgrass et al [41]) or patterns (i.e. specific graphic combinations [31] [47]) which participants had to recognize. The studies were based on comparative studies involving people with different visual capacities, such as early blind, late blind and sighted people, which showed contradictory results.…”
Section: Recognition Of Tactile Graphicsmentioning
confidence: 99%
“…Unlike Zhang's (2020) haptic device prototype namely Tapsonic, two linear actuators were used to be mounted on the top and bottom of the index and middle fingers [5]. Zhao et. al (2020) had identified that the back of the hand was more convenient to place four vibrating mini motor discs to deliver eight different vibrations patterns for the purpose of digital image exploration [6].…”
Section: Related Workmentioning
confidence: 99%
“…Zhao et. al (2020) had identified that the back of the hand was more convenient to place four vibrating mini motor discs to deliver eight different vibrations patterns for the purpose of digital image exploration [6].…”
Section: Related Workmentioning
confidence: 99%